LGG-35. IDENTIFICATION OF SETD2 MUTATION IN AN AGGRESSIVE PILOCYTIC ASTROCYTOMA PRESENTING AS AN INFLAMMATORY OPTIC NERVE LESION. Issue 2 (22nd June 2018) - Gartrell, Robyn; Omesi, Lenore; Silverman, Andrew; Campbell, Ashley; Feldstein, Neil; Saenger, Yvonne; Mansukhani, Mahesh; Zanazzi, George; Canoll, Peter; Kazim, Michael; Garvin, James
Abstract: Optic nerve glioma (ONG) in childhood has variable clinical behavior despite uniform histology (grade 1 pilocytic astrocytoma). We report a previously healthy male child who presented at age 19 months with fever, unilateral proptosis, and fixed dilated pupil with no light perception. MRI showed unilateral optic nerve enlargement in the orbit and optic canal, with gadolinium enhancement and restricted diffusion. Biopsy showed degenerated optic nerve, fibro-adipose tissue, reactive astrocytes, and an inflammatory infiltrate of T-lymphocytes and microglia, but did not support a diagnosis of ONG. The lesion regressed on dexamethasone, but progressed 17 months later in the infra-orbital and pre-chiasmatic optic nerve. Orbital and intracranial biopsy specimens showed pilocytic astrocytoma, with focally increased proliferative index (10.4%) intracranially. Both specimens contained KIAA1549-BRAF fusions. Treatment with vincristine and carboplatin resulted in tumor stabilization and preservation of vision in the opposite eye. Molecular testing (Columbia Combined Cancer Panel) showed a SETD2 nonsense mutation (p.R2040*) in the intra-orbital and intracranial tumor, but also in the initial biopsy specimen at first presentation (variant allelic fraction 27%). SETD2 mutation has been reported in hemispheric high-grade glioma but not ONG. All three specimens have been stained using quantitative multiplex immunofluorescence (qmIF) to evaluate for CD3, CD8, CD68, HLA-DR, SETD2, and Olig2. QmIF analysis is underway to quantify immune phenotypes and evaluate for loss of SETD2 expression on Olig2 positive tumor cells. In this unusual case, serial molecular characterization retrospectively detected a glioma-associated mutation in advance of clinical progression and histologic diagnosis of an aggressive ONG.